Comparing Indonesian and English Culture in EFL Context - Giyatmi; Sihindun Arumi; Purwani Indri Astuti; Ratih Wijayava (Formosa Journal of Sustainable Research, 2022)
This research aims at describing the implementation of comparing Indonesian and English culture in EFL context and describing the students’ perception on it. This is a descriptive qualitative.  This research is applied to non-English department in English lesson. The data used in this research is the questionnaire results. To collect the data, the writer gives questionnaire to the students via Google Form. The writer uses 4 topic of cultural material such as comparing fairy tale (Bawang Merah Bawang Putih VS Cinderella), tradition (The Night of  One Suro VS Halloween), Indonesian VS English proverbs, and Food around the world (Acar/Pickle).  The students feel interest and enjoy with all materials. Even after learning those materials, they are proud of Indonesian culture.